Ibn al-Muʿtazz the Epigrammatist: Some Notes on Length and Genre of Ibn al-Muʿtazz’s Short Poems - Papoutsakis, Nefeli (Oriens, 2012)
Abstract This paper demonstrates the importance of short forms — couplets, triplets and quatrains — in the work of the Abbasid poet Ibn al-Muʿtazz (861-908) and highlights the key role he played in the proliferation of the two-liner. It discusses the scholarly editions of his dīwān, offers statistical data regarding the frequency of the various short forms and comments on the arrangement of the poems in his dīwān. The discussion of a highly selective sample of couplets and triplets shows how epigrammatic expression blurred the generic identity of short poems.